Application of adrenocorticotropic hormone in recurrent focal segmental glomerulosclerosis post‐transplantation: A case report and literature review. (1st November 2021) - Chen, Lizhi; Wu, Jingyi; Ying, Daojing; Jiang, Mengjie; Xu, Yuanyuan; Mo, Ying; Rong, Liping; Jiang, Xiaoyun
Abstract: Background: The recurrence rate of focal segmental glomerulosclerosis (FSGS) post‐renal transplantation is as high as 30%–50%. However, the pathogenesis is unclear. At present, there is no unified standard for the treatment of recurrent FSGS post‐transplantation. Its treatment is full of risks and challenges. Methods: We report a child with recurrent FSGS with massive proteinuria 6 9 g/m 2 /day and resistance to plasma exchange (PE) and rituximab (RTX). On the basis of receiving anti‐rejection therapy of prednisone, tacrolimus, and mycophenolate mofetil (MMF), we treated the child with adrenocorticotropic hormone (ACTH), and reviewed the literature on the application of ACTH in the recurrence of FSGS post‐transplantation. Results: After 1 year of treatment with ACTH, the patient's urinary protein decreased and fluctuated between 0.6 and 1.1 g/m 2 /day. The albumin (ALB) and cholesterol (CHOL) returned to the normal range. The patient achieved complete remission after 19 months of ACTH treatment and maintained until now. There was no obvious adverse reaction. Literature review showed that up to February 2021, a total of 8 studies showed the use of ACTH in kidney transplant patients, and all the patients in the study achieved remission. Conclusions: ACTH is a potential option for treating recurrent FSGS post‐transplantation with fewer side effects and relatively safe for patients. However, further evaluation is needed to better adapt to different populations.